Safety, Pharmacokinetics, and Causal Prophylactic Efficacy of KAF156 in a Plasmodium falciparum Human Infection Study - Kublin, James G; Murphy, Sean C; Maenza, Janine; Seilie, Annette M; Jain, Jay Prakash; Berger, David; Spera, Danielle; Zhao, Rong; Soon, Rachel L; Czartoski, Julie L; Potochnic, Meredith A; Duke, Elizabeth; et al. (Clinical infectious diseases, 2021)
KAF156 is a novel antimalarial drug that is active against both liver- and blood-stage Plasmodium parasites, including drug-resistant strains. Here, we investigated the causal prophylactic efficacy of KAF156 in a controlled human malaria infection (CHMI) model. In part 1, healthy, malaria-naive participants received 800 mg KAF156 or placebo 3 hours before CHMI with P. falciparum-infected mosquitoes. In part 2, KAF156 was administered as single doses of 800, 300, 100, 50, or 20 mg 21 hours post-CHMI. All participants received atovaquone/proguanil treatment if blood-stage infection was detected or on day 29. For each cohort, 7-14 subjects were enrolled to KAF156 treatment and up to 4 subjects to placebo. KAF156 at all dose levels was safe and well tolerated. Two serious adverse events were reported-both resolved without sequelae and neither was considered related to KAF156. In part 1, all participants treated with KAF156 and none of those randomized to placebo were protected against malaria infection. In part 2, all participants treated with placebo or 20 mg KAF156 developed malaria infection. In contrast, 50 mg KAF156 protected 3 of 14 participants from infection, and doses of 800, 300, and 100 mg KAF156 protected all subjects against infection. An exposure-response analysis suggested that a 24-hour postdose concentration of KAF156 of 21.5 ng/mL (90% confidence interval, 17.66-25.32 ng/mL) would ensure a 95% chance of protection from malaria parasite infection. KAF156 was safe and well tolerated and demonstrated high levels of pre- and post-CHMI protective efficacy. NCT04072302.